2022
DOI: 10.31083/j.jin2101021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stevia rebaudiana Bertoni extracts in the rat model of epilepsy induced by pentylenetetrazol: Sirt-1, at the crossroads between inflammation and apoptosis

Abstract: The current study investigated the e fects of stevia extracts on a PTZinduced epileptic rat model and its potential mechanism. Thirty male Sprague-Dawley rats were equally subdivided into 3 groups; (1) normal control (NC) group, (2) PTZ-group: received PTZ (50 mg/kg, i.p. every other day) for 2 weeks, and (3) PTZ+ Stevia group: received PTZ and stevia (200 mg/kg orally daily) for 4 weeks (2 weeks before the start of PTZ treatment and 2 weeks with PTZ administration). The first jerk latency and the seizure scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Studies on seizures during EP have shown an up-regulation of TP53 and CASP3 in the brain; genetic elimination or pharmacologic suppression of TP53 can alleviate seizure-induced cell apoptosis. [38] BPs enriched through GO analysis include responses to oxidative stress, neuronal death, regulation of the extrinsic apoptotic signaling pathway, and postsynaptic signal transduction. The KEGG enrichment analysis indicates that the signaling pathways of ATR-NRR intervention in EP are mainly related to oxidative stress, inflammation, programmed cell death pathways, including the PI3K-Akt, IL-17, TNF, and apoptosis signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on seizures during EP have shown an up-regulation of TP53 and CASP3 in the brain; genetic elimination or pharmacologic suppression of TP53 can alleviate seizure-induced cell apoptosis. [38] BPs enriched through GO analysis include responses to oxidative stress, neuronal death, regulation of the extrinsic apoptotic signaling pathway, and postsynaptic signal transduction. The KEGG enrichment analysis indicates that the signaling pathways of ATR-NRR intervention in EP are mainly related to oxidative stress, inflammation, programmed cell death pathways, including the PI3K-Akt, IL-17, TNF, and apoptosis signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on seizures during EP have shown an up-regulation of TP53 and CASP3 in the brain; genetic elimination or pharmacologic suppression of TP53 can alleviate seizure-induced cell apoptosis. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…The ferric reducing antioxidant power (FRAP) assay [40] is based on the ability of antioxidants to reduce ferric ion Fe +3 to ferrous ion Fe +2 in a redox reaction, the Fe +2 then reacts with the colorimetric reagent TPTZ (2,4,6-tripyridyl-s-triazine, and iron(III) chloride hexahydrate) to produce a complex which can be measured spectrophotometrically at 593 nm. In one study [41], TAC was indirectly measured by determining the residual H 2 O 2 through the conversion of 3,5, dichloro dicloro-2-hydroxy benzensulphonate to a colored product. The measurement of this colored product can be measured spectrophotometrically at 500-510 nm.…”
Section: Data Extraction and Antioxidant Markersmentioning
confidence: 99%
“…A thorough literature search for antioxidant activity of stevia resulted in 184 articles. After screening of titles and abstracts, and compliance with the PRISMA guidelines (http://www.prisma-statement.org/ (accessed on 26 January 2023)) (Figure 2), 22 articles were found to satisfy the eligibility criteria [41,42,44,45,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]. Seventeen records were additionally retrieved from screening lists of references, and two of them [37,73] were enrolled in the meta-analysis, making a total of 24 articles, which contained 104 studies in total.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…SGs are gaining popularity as sweeteners due to their confirmed health benefits in vivo and in vitro. Besides the sweet taste, stevia extract and SGs demonstrate therapeutic benefits as a joint nutraceutical in the management of chronic diseases including overweight and obesity, diabetes mellitus, fatty liver, cardiac fibrosis, liver fibrosis, inflammatory bowel disease, certain types of cancer, hypertension, and chronic kidney diseases (reviewed in [4]), and they exhibit neuroprotective and antiepileptic activity [5]. SGs are gaining popularity as sweeteners due to their confirmed health benefi vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%